Ovire sodelovanja bolnikov pri zdravljenju - Petek, Davorina (Medicinski razgledi, 2002)
Adherence to treatment is especially important for patients with a chronic illness. The emphasis is on the active cooperation of the patient in the treatment process, not just his passive submission to doctors' instructions. Most studies conclude that poor compliance is to be expected in 30-50% of patients with a chronic illness. The measurements of compliance can be direct (detection of a chemical metabolite) or indirect-like interviews and other self report methods. No method gives valid and reliable data for measuring of compliance. Numerous variables (sociodemographic, treatment factors, economic factors) have been studied as possible causes of poor adherence, but none of them is consistently related to adherence. Patient health beliefs seem important in this context. Several interventions have been investigated to improve patient adherence, including reminders, education, fewer doses per day, diminishing practical obstacles in access to check-ups or organisation ofhelp in the family. Doctor-patient relationship and communication are identified as an important issue.
Keywords: Bolnik, sodelovanje; Patient Compliance; Bolnik, sprejetje zdravstvene oskrbe; Patient Acceptance Of Health Care; Physician-Patient Relations; Zdravnik-bolnik, odnosi; therapy; zdravljenje; zdravstvena oskrba; bolniki; sodelovanje